렘수면 의존성 수면무호흡증과 비렘수면 의존성 수면무호흡증의 특징 - 서민철, 최재원, 주은정, 이규영, 방수영, 김의중 (Sumyŏn--chŏngsin saengni, 2017)
Objectives: Obstructive sleep apnea (OSA) is a sleep-related breathing disorder that is characterized by repetitive collapse or partial collapse of the upper airway during sleep in spite of ongoing effort to breathe. It is believed that OSA is usually worsened in REM sleep, because muscle tone is suppressed during REM sleep. However, many cases showed a higher apnea-hypopnea index (AHI) during NREM sleep than during REM sleep. We aimed here to determine the characteristics of REM sleep-dependent OSA (REM-OSA) and NREM sleep-dependent OSA (NREM-OSA). Methods: Five hundred sixty polysomnographically confirmed adult OSA subjects were studied retrospectively. All patients were classified into 3 groups based on the ratio between REM-AHI and NREM-AHI. REM-OSA was defined as REM-AHI/NREM-AHI > 2, NREM-OSA as NREM-AHI/REM-AHI > 2, and the rest as sleep stage-independent OSA (IND-OSA). In addition to polysomnography, questionnaires related to subjective sleep quality, daytime sleepiness, and emotion were completed. Chi-square test, ANOVA, and ANCOVA were performed. Results: There was no age difference among subgroups. The REM-OSA group was comprised of large proportions of mild OSA and female OSA patients. These patients experienced poor sleep and more negative emotions than other two groups. The AHI and oxygen desaturation index (ODI) were lowest in REM-OSA. Sleep efficiency and N3 percentage of REM-OSA were higher than in NREM-OSA. The percentage of patients who slept in a supine position was higher in REM-OSA than other subgroups. IND-OSA showed higher BMI and larger neck circumference and abdominal circumference than REM-OSA. The patients with IND-OSA experienced more sleepiness than the other groups. AHI and ODI were highest in IND-OSA. NREM-OSA presented the shortest total sleep time and the lowest sleep efficiency. NREM-OSA showed shorter sleep latency and REM latency and higher percentage of N1 than those of REM-OSA and the highest proportion of those who slept in a lateral position than other subgroups. NREM-OSA revealed the highest composite score on the Horne and ${\ddot{O}}stberg$ questionnaire. With increased AHI severity, the numbers of apnea and hypopnea events during REM sleep decreased, and the numbers of apnea and hypopnea events during NREM sleep increased. The results of ANCOVA after controlling age, sex, BMI, NC, AC, and AHI showed the lowest sleep efficiency, the highest AHI in the supine position, and the highest percentage of waking after sleep onset in NREM-OSA. Conclusion: REM-OSA was associated with the mild form of OSA, female sex, and negative emotions. IND-OSA was associated with the severe form of OSA. NREM-OSA was most closely related to position and showed the lowest sleep efficiency. Sleep stage-dependent characteristics could provide better understanding of OSA. 목 적 : 폐쇄성 수면무호흡증(obstructive sleep apnea)은 수면 시 호흡을 하려고 하는 노력에도 불구하고 기도의 부분적/완전 폐색이 반복되는 수면 관련 호흡 질환이다. 일반적으로 렘수면에서 근긴장도의 저하가 나타나게 되므로 렘수면에서 수면무호흡증의 악화가 예상되지만 많은 경우에 있어 비렘수면에서의 무호흡/저호흡 지수(apnea-hypopnea index, AHI)가 렘수면에서의 AHI보다 높은 경우가 관찰되었다. 그러나 그런 현상의 분명한 이유는 밝혀져 있지 않았기에 렘/비렘수면 의존성 수면무호흡증에 대한 특징을 종합적으로 알아보고자 하였다. 방 법 : 560명의 성인 수면무호흡증 환자를 대상으로 후향적 연구를 진행하였다. 모든 환자는 렘 수면시의 AHI (REM-AHI), 비렘수면시의 AHI (NREM-AHI)의 비율에 따라 세군으로 분류하였다. 렘수면 의존성 수면무호흡증(REM sleep dependent OSA, REM-OSA)는 REM-AHI/NREMAHI > 2, 비렘수면 의존성 수면무호흡증(NREM sleep dependent OSA, NREM-OSA)는 NREM-AHI/REM-AHI > 2, 수면 단계 비의존성 수면무호흡증(Sleep stage independent OSA, IND-OSA)로 분류하였다. 수면다원검사 이외에도 주관적인 수면의 질, 낮시간 졸림, 정서와 연관된 설문지를 함께 시행하였다. 카이제곱 검정, 일원배치분산분석, 공분산분석을 시행하였다. 결 과 : 세 군 사이에서 연령의 차이는 보이지 않았다. REM-OSA는 대체로 경도의 수면무호흡증 환자가 많았고 여성의 비율이 가장 높았다. 또한 주관적인 수면의 질이 가장 저하되어 있다고 느꼈으며 기분 상태 평가 척도인 K-POMS의 점수는 가장 높았다. IND-OSA는 BMI, 목둘레(neck circumference, NC), 복부 둘레(abdominal circumfefence)가 REM-OSA에 비해 높았고 주간 졸림의 호소는 세군 중 가장 컸고, 무호흡 관련 변인의 값이 가장 높아 중증도가 심한 군이었다. 공변량을 통제하고 시행한 공분산 분석의 결과에서 NREM-OSA는 앙와위에서의 AHI가 가장 높았고 수면 중 측와위의 비율이 가장 컸다. 또한 수면 효율이 가장 떨어졌고 렘수면 잠복기가 가장 길었으며 입면 후 각성 시간의 비율이 가장 컸다. 결 론 : REM-OSA는 여성이 많고 부정적인 정서를 가장 많이 호소하는 군으로, 경도의 수면무호흡증을 가장 많이 포함하였고 IND-OSA는 중증의 수면무호흡증을 반영하였다. NREM-OSA는 자세 변화와 가장 밀접한 관련은 지니고 있었으며 수면 효율이 가장 떨어졌다. 세 군의 수면무호흡증이 일련의 중중도 차이만이 아닌 또 다른 특성을 반영하는 것으로 보이고 이를 통해 폐쇄성 수면무호흡증의 이해를 넓힐 수 있을 것이다.